Synthesis and photocatalytic performance of g-C3N4/MeTMC-COP composite photocatalyst - Cao, Lili; Qiao, Songli; Li, Xue; Li, Qiang (Frontiers in Chemistry, 2023)
Covalent organic polymers have excellent application prospects in photocatalysis due to their excellent visible light absorption and structural designability. However, their fast recombination efficiency and complex preparation process limit their applications. Because of the above problems, this paper used urea to prepare g-C3N4 by high-temperature thermal polymerization and prepared g-C3N4 composite photocatalyst loaded with MeTMC-COP (g-C3N4/MeTMC-COP) by hydrothermal method. The photocatalytic hydrogen generation and photocatalytic degradation capabilities of composite photocatalysts with various mass ratios were investigated by characterizing the catalyst and using the organic dye Rhodamine B (RhB) as the pollutant. According to the research, the specific surface area of the g-C3N4/MeTMC-COP composite may reach 40.95 m2 g−1 when the mass ratio of g-C3N4 and MeTMC-COP is 3:1 (25.22 m2 g−1). It can offer more active sites for the photocatalytic process, and because the fluorescence peak intensity is the lowest, it has the lowest photogenerated electron-hole recombination efficiency. In comparison to g-C3N4, 3:1 g-C3N4/MeTMC-COP can breakdown rhodamine B up to 100% after 75 min of light irradiation; its photocatalytic hydrogen generation efficiency is 1.62 times that of g-C3N4, and the hydrogen evolution rate is 11.8 μmol g−1 h−1.